Palynomorphological characteristics of the genus Puccinellia Parl. (Poaceae) species of the flora of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The pollen morphology of six Puccinellia species of the Ukrainian flora using light and scanning electron microscopy was studied. The detailed morphological characteristics are represented. The pollen grains of species P. brachylepis were studied for the first time. It was found that the size of pollen grains and anther length are vary and it probably depends on ecological factors, therefore these features can not be diagnostic for species. Study of pollen grains of P. distans from different habitat conditions have not allowed us to confirm existing data regarding anther form (Yu.M. Prokudin indicates that P. distans differs from all other species of anthers elliptic shape. In all studied species the anther form was linear).
Keywords: pollen grains, Puccinellia, flora Ukraine.